Community currencies: A new tool for sustainable consumptions? - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
Sustainable consumption is gaining currency as a new environmental policy objective, but there is a limit to the changes in consumption behaviour which individuals can make within current socio-economic frameworks. The 'new economics' literature argues that sustainable consumption is characterised by five factors: localisation, reducing ecological footprints, community-building, collective action, and building new social institutions. These form a set of indicators for evaluation of initiatives and policies. Community currencies have been put forward as a new tool to promote sustainable consumption, but until now there has been no appraisal of their ability to deliver this goal. Three different community currency types are described and their effectiveness and potential in enabling more sustainable consumption patterns is assessed against this set of indicators. The currencies examined are: Local Exchange Trading Schemes (LETS) which aims to rebuild local economies through cashless exchange; Time Banks promote volunteering, civic engagement and mutual self-help by rewarding unpaid work in the community; and the previously unresearched NU-card, a 'green loyalty point' currency which incentivises sustainable consumption. The findings of this preliminary analysis indicate that while they all represent nascent social institutions based on different sets of values to the mainstream, each model of community currency successfully achieves some, but not all, of the criteria for sustainable consumption. However, the currencies are complementary and between them each of the indicators is met. The policy and research implications of the study are discussed.
Keywords: 330; community currencies; economic systems; environmental governance; institutions; localisation; sustainable consumption